The impact of eating disorder risk on sports anxiety and sports confidence in Division III female athletes - Barbieri Bullard, J.-A. (The Sport Journal, 2015)
Eating disorder risk is important to assess not only regarding possible impact on the performance ability of an athlete, but also for the health risks athletes could experience. The purpose of this study is to evaluate eating disorder risk and the impact on sports anxiety and sports confidence of Division III female student-athletes. The results were based off of the Eating Attitudes Risk-26 Questionnaire to examine eating disorder risk, the Sport Anxiety Scale-2 to examine trait anxiety in sport settings, and the Sources of Sport Confidence Questionnaire to examine sources of sport confidence. The methodology included an informed consent form, demographics questionnaire, Eating Attitudes Risk-26 Questionnaire, Sport Anxiety Scale-2, and the Sources of Sport Confidence Questionnaire. Analyses were completed utilizing bivariate correlations and regression analysis. The results of this study showed that eating disorder risk was significantly correlated with only one variable of sports confidence, labeled as physical self-presentation, and no variables of sports anxiety. Athletic departments, athletic trainers and coaching staffs can utilize these findings to effectively work with student-athletes in a preventative manner.